2018
DOI: 10.1007/s00066-018-1345-8
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicine in radiation oncology

Abstract: Today, CAM is integrated into cancer care; however, skepticism regarding its effect still exists. Evidence-based results must be generated to convince physicians of the effectiveness of CAM methods. CAM qualifications must be included in physicians' training to improve their understanding and counseling regarding CAM options in cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…The Working Group on Integrative Medicine of the German Society of Gynecological Oncology earlier developed a questionnaire for gynecological oncologists to evaluate the degree of acceptance, usage, and implementation of IM. The questionnaire was successfully distributed in 2014 to all members of the German Society of Gynecological Oncology in the German Cancer Society (DKG), with a focus on gynecological oncologists working in hospitals [7,19]. The study showed that there is considerable interest in IM among gynecological oncologists, but that IM therapy approaches were poorly implemented in routine clinical work (25%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Working Group on Integrative Medicine of the German Society of Gynecological Oncology earlier developed a questionnaire for gynecological oncologists to evaluate the degree of acceptance, usage, and implementation of IM. The questionnaire was successfully distributed in 2014 to all members of the German Society of Gynecological Oncology in the German Cancer Society (DKG), with a focus on gynecological oncologists working in hospitals [7,19]. The study showed that there is considerable interest in IM among gynecological oncologists, but that IM therapy approaches were poorly implemented in routine clinical work (25%).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from 2014 on IM in radiotherapy in Germany showed that for 32.2% of gynecological oncologists, IM is part of routine treatment (not part of it, 57.3%; unknown, 10.5%) and that 22.0% were planning to incorporate it [7]. Like the Society of Gynecology and Obstetrics, the German Society of Radio-Oncology and Radiotherapy (Deutsche Gesellschaft für Radioonkologie, DEGRO) has recently set up a guideline commission for IM, and radiation oncology is a key field in this context [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous self-report studies show that one of the biggest hurdles that oncologists experience is not having enough knowledge on the topic. 4 , 19 - 22 …”
Section: Introductionmentioning
confidence: 99%
“… 32 From the healthcare providers’ side, the main reasons mentioned to explain why CM is not further integrated into oncological care were missing evidence, financial resources and qualifications. 21 , 33 , 34 …”
Section: Introductionmentioning
confidence: 99%